In vivo optical coherence tomography of experimental thrombosis in a rabbit carotid model. Issue 6 (18th October 2007) - Meng, L; Lv, B; Zhang, S; Yv, B
Abstract : Background: Plaque rupture with subsequent thrombosis is recognised as the underlying pathophysiology of most acute coronary syndromes. Thus, direct thrombus visualisation in vivo may be beneficial for both diagnosis and guidance of therapy. We sought to test the feasibility of imaging acute thrombosis in vivo using optical coherence tomography (OCT) in an experimental thrombosis animal model. Methods and results: Nine male New Zealand White rabbits (weight ≈3.0 kg) were made atherosclerotic with a high-cholesterol diet after injury of the right carotid artery endothelium. Thrombus was then induced with the use of Russell's viper venom (RVV) and histamine. Subsequently, OCT imaging of the right carotid artery was performed. Histology was performed on arterial regions that were injured by balloon. Six rabbits (67%) developed thrombus. Histological correlation confirmed all thrombi (100%) detected with OCT, with no other thrombi seen in the other regions of the right carotid artery. In the remaining three rabbits, no thrombus was observed by OCT or histology. Conclusion: We demonstrate the feasibility of OCT for the detection of acute thrombosis in vivo using an animal model of atherosclerosis and acute thrombosis. Potential clinical applications include thrombus detection in acute coronary syndromes.